Evolução da coloração da plumagem e dimorfismo sexual em passeriformes - Teófilo, Fernando (Instituto Nacional de Pesquisas da Amazônia - INPA, 2021)
The plumage color is one of the most commonly visual cues used in communication contexts and can role adaptive and reproductive functions. In birds, color diversity and mechanisms of color production can be observed on a large scale; among species, among populations of the same species or even among individuals of the same population. Thus, hypotheses based on natural and/or sexual selection mechanisms have sought to explain the evolution of these traits, especially in polygynous clades (e.g., quality indicator, Fisher runaway selection and sensory direction). However, it is a little known on the relative importance of these evolutionary mechanisms in the evolution of plumage at different levels- in species and intrapopulation. This thesis investigated these issues using passerine species as focal species. The hypothesis was tested that sexual dichromatism was related to the evolution of plumage conspicuity of 26 monomorphic bird species to human vision, modeling the color variation for bird vision. Furthermore, this thesis investigated the role of parasites in the evolution of plumage staining of a passerine species, blue-crowned manakin (Lepidothrix coronata), and the relationship of male plumage color of this species with the frequency off emale visits. In chapter 1, it is shown that the pattern of sexual dichromatism is related to the plumage conspicuousness of the passerine species, indicating an important role of sexual selection in the evolution of color differences between the sexes. In Chapter 2, the selective role of sexual selection in the evolution of L. coronata plumage is revealed, so that the conspicuous plumage coloration of males of this species attracts more females although it does not indicate susceptibility to parasites causing avian malaria. Thus, this thesis highlights the evolution of plumage at different scales of variation (between sexes of the same species and between individuals of the same population) and suggests that mechanisms of sexual selection play an important role in the morphological variation of these phenotypic traits in these species.
Keywords: Seleção sexual; coloração; evolução; ecologia; aves; seleção natural